University Students’ Perceptions on Note-Taking and Its Impact on Academic Performance - Kitjaroonchai, Nakhon; Marshall, Prema; Phasook, Jirapa; Thararuenroeng, Nadtawadee (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2025)
This study investigated university students’ perceptions of note-taking and its potential impact on academic performance, as well as the factors influencing their note-taking decisions. The participants included 150 students, comprising 75 Thai and 75 non-Thai students enrolled at Asia-Pacific International University, Thailand, during the second semester of the 2023-2024 academic year. The research instrument was a survey questionnaire featuring a five-point Likert scale and an open-ended question to assess students' perceptions of the relationship between note-taking and academic performance, along with the factors affecting their note-taking decisions. The results indicated a widespread belief in the effectiveness of note-taking among participants, suggesting a consensus on its positive role in academic achievement. Additionally, the open-ended responses revealed perceived benefits of note-taking for memory enhancement, improved comprehension, academic achievement, and content simplification. This study highlights the need for further exploration of the nuanced factors influencing student academic success.